Norepinephrine transporter expression is inversely associated with glycaemic indices: a pilot study in metabolically diverse persons with overweight and obesity. (19th January 2016) - Straznicky, N. E.; Guo, L.; Corcoran, S. J.; Esler, M. D.; Phillips, S. E.; Sari, C. I.; Grima, M. T.; Karapanagiotidis, S.; Wong, C. Y.; Eikelis, N.; Mariani, J. A.; Kobayashi, D.; et al.
Summary: Objective: The objective of this study was to examine the cross‐sectional relationship between the expression of norepinephrine transporter (NET), the protein responsible for neuronal uptake‐1, and indices of glycaemia and hyperinsulinaemia, in overweight and obese individuals. Methods: Thirteen non‐medicated, non‐smoking subjects, aged 58 ± 1 years (mean ± standard error of the mean), body mass index (BMI) 31.4 ± 1.0 kg m −2, with wide‐ranging plasma glucose and haemoglobin A1c (HbA1c, range 5.1% to 6.5%) participated. They underwent forearm vein biopsy to access sympathetic nerves for the quantification of NET by Western blot, oral glucose tolerance test (OGTT), euglycaemic hyperinsulinaemic clamp, echocardiography and assessments of whole‐body norepinephrine kinetics and muscle sympathetic nerve activity. Results: Norepinephrine transporter expression was inversely associated with fasting plasma glucose ( r = −0.62, P = 0.02), glucose area under the curve during OGTT (AUC0–120, r = −0.65, P = 0.02) and HbA1c ( r = −0.67, P = 0.01), and positively associated with steady‐state glucose utilization during euglycaemic clamp ( r = 0.58, P = 0.04). Moreover, NET expression was inversely related to left ventricular posterior wall dimensions ( r = −0.64, P = 0.02) and heart rate ( r = −0.55, P = 0.05). Indices of hyperinsulinaemia were not associated with NET expression. In stepwise linear regression analysis adjusted for age, body mass index and blood pressure, HbA1c was an independent inverse predictor of NET expression, explaining 45% of its variance. Conclusions: Hyperglycaemia is associated with reduced peripheral NET expression. Further studies are required to identify the direction of causality. Abstract : The norepinephrine transporter (NET) plays an important role in the re‐uptake of norepinephrine (NE) from the sympathetic neuroeffector junction and to a lesser extent from the general circulation (uptake‐1). This cross‐sectional study demonstrates an inverse relationship between glycaemic indices and peripheral NET expression in metabolically diverse persons with overweight and obesity. These findings are clinically relevant because impairment of uptake‐1 augments the sympathetic neural signal with potential deleterious effects on cardiovascular and metabolic regulation.